(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Dwifajri S, Tapilatu RF, Pranata B, Kusuma AB. 2022. Molecular phylogeny of grouper of Epinephelusgenus in Jayapura, Papua, Indonesiainferred from Cytochrome Oxidase I (COI) gene. Biodiversitas 23: 1449-1456. Grouper (Serranidae: Epinephelinae: Epinephelus) fish have high economic value, and are relatively overfis hed, yet have not received serious attention to determine conservation status by the International Union for Conservation of Nature (IUCN). DNA barcoding is an important molecular approach to identify Papua’s grouper species. The objective of the present study was to analyze species diversity and molecular phylogeny of Epinephelus grouper based on DNA sequences of mitochondrial control region COI gene. Samples of grouper fish were collected from Hamadi, Sentani, and Youtefa local fish markets in Jayapura, Papua during August 2020. Grouper was morphologically identified, photographed and its fin was clipped and preserved for molecular analysis. Present study used primers, i.e., Fish R1 5’TAGACTTCTGGCCAAGAATCA3’ and Fish F1 5’TCAACCAACCACAAAGACATTGGCA3’. Based on gene bank comparison at the sequence length 689 base pairs, the present study obtained seven species of grouper (Serranidae: Epinephelinae), namely Epinephelus areolatus, Epinephelus coioides, Epinephelus episictus, Epinephelus kupangensis, Epinephelus macrospilos, Epinephelus melanostigma and Epinephelus merra. The phylogenetic tree was composed of seven clades, where each grouper species represented each clade. The genetic distance between Epinephelus kupangensis and Epinephelus melanostigma was determined as the closest genetic distance (0.123) in the present study, while the farthest one was found between Epinephelus episictus and Epinephelus merra (0.161).